JUDICIAL ACTIVISM DURING MUSHARAF REGIME AND ITS IMPACT ON PAKISTAN’S SOCIETY (Contemporary Journal of Social Science Review, 2024)
Activism on the part of the judiciary can take many forms. Generally, judges should make their decisions based on the law, rules, and regulations governing the case and not on their personal opinions or viewpoints. Main purpose of this study is to investigate the impact of judicial activism on Pakistani society as whole and to judge whether judicial activism is in accordance with the constitution of Pakistan 1973. Methods used in this study include both qualitative and quantitative approaches. To assess the perception of Pakistani people regarding judicial activism, researchers conducted a survey. People from different professions, including lawyers, law students, public policy students, and others, were the target population for sampling. According to 95% of respondents, the judiciary in Pakistan is not performing its functions properly in response to a statement about its functioning. Media played a significant role in promoting judicial activism during Musharaf's rule, according to 91% of respondents. During Musharaf's rule, 88% of people believe that some judges misused their constitutional powers. A large number of people, 92 %, agree that judges decide matters using discretionary powers, meaning that they do not decide matters based on their own preferences, but rather based on the circumstances and situation of the case as well as within the law's scope. A true spirit of justice cannot be achieved without deciding millions of cases that are pending. A significant portion of the Supreme Court's work focused on undermining parliament and the administration, while the basic duty to provide justice in a timely manner was ignored.